TREATMENT OPTIMIZATION IN RECURRENT DERMATOPHYTOSIS: A PROSPECTIVE, RANDOMIZED, COMPARATIVE STUDY OF EXTENDED-DURATION VERSUS HIGH-DOSE TERBINAFINE AND ITRACONAZOLE - SINGH, RASHI; VERMA, SAVITA; DAYAL, SURABHI; VASHISTH, SAPNA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To compare efficacy and safety of terbinafine versus itraconazole administered in double dose and prolonged duration in patients with recurrent tinea corporis and cruris. Methods: This prospective, randomized study included 166 patients in four groups: A (terbinafine 250 mg once daily (OD), 4 w), B (terbinafine 500 mg OD, 2 w), C (itraconazole 100 mg twice daily (BD), 4 w), and D (itraconazole 200 mg BD, 2 w). Primary outcomes were clinical/mycological cure, global assessment, safety; secondary outcomes included quality of life, escape treatment, adherence. Significance was set at p<0.05. Results: Group C had highest efficacy (92.7% clinical cure and 100% mycological cure) with lowest recurrence. Liver Function Tests (LFTs) showed no significant abnormalities across all groups. No therapy discontinuations/serious Adverse Drug Reactions (ADRs) were reported. Dermatology Life Quality Index (DLQI) improved significantly from baseline to treatment end and 6 w post-treatment, indicating substantial and sustained improvement. Treatment compliance was high across all groups (≥90%), with no significant difference. Conclusion: Itraconazole 100 mg BD for 4 w was most effective, well-tolerated regimen, highlighting benefit of extended duration over increased dose in recurrent dermatophytosis.